2015
DOI: 10.1021/acs.jmedchem.5b00931
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Purines and 7-Deazapurines as Potent and Selective Type I Inhibitors of Troponin I-Interacting Kinase (TNNI3K)

Abstract: A series of cardiac troponin I-interacting kinase (TNNI3K) inhibitors arising from 3-((9H-purin-6-yl)amino)-N-methyl-benzenesulfonamide (1) is disclosed along with fundamental structure-function relationships that delineate the role of each element of 1 for TNNI3K recognition. An X-ray structure of 1 bound to TNNI3K confirmed its Type I binding mode and is used to rationalize the structure-activity relationship and employed to design potent, selective, and orally bioavailable TNNI3K inhibitors. Identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(83 citation statements)
references
References 46 publications
0
78
0
Order By: Relevance
“…In the present report, GSK114 is similar to 7-deazapurine in structure, which may be also a new inhibitor of TNNI3K [34]. Importantly, the specificity of GSK114 for TNNI3K translated into the cellular context, as GSK114 exhibited IC 50 = 3300 nM in a cell assay employing B-Raf compared to IC 50 = 100 nM in the TNNI3K cell assay [34, 35]. Recent studies have demonstrated that mi R-223 with antioxidant protein 1 (AOP-1), which is a mitochondrial antioxidant protein [36], can suppress cardiomyocyte hypertrophy via down-regulation of cTnI phosphorylation, which reduces intracellular Ca 2+ and the contractility of cardiomyocytes by directly targeting TNNI3K [37].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present report, GSK114 is similar to 7-deazapurine in structure, which may be also a new inhibitor of TNNI3K [34]. Importantly, the specificity of GSK114 for TNNI3K translated into the cellular context, as GSK114 exhibited IC 50 = 3300 nM in a cell assay employing B-Raf compared to IC 50 = 100 nM in the TNNI3K cell assay [34, 35]. Recent studies have demonstrated that mi R-223 with antioxidant protein 1 (AOP-1), which is a mitochondrial antioxidant protein [36], can suppress cardiomyocyte hypertrophy via down-regulation of cTnI phosphorylation, which reduces intracellular Ca 2+ and the contractility of cardiomyocytes by directly targeting TNNI3K [37].…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly a series of small-molecule TNNI3K inhibitors were used to reduce mitochondrial-derived superoxide generation, p38 activation, and infarct size when delivered at reperfusion to mimic clinical intervention [15, 34]. Currently, 7-deazapurine, which is potent and selective type I inhibitors of TNNI3K, are used to elucidate the role of TNNI3K in cardiac biology and used for the development of novel heart failure medicines [35]. In the present report, GSK114 is similar to 7-deazapurine in structure, which may be also a new inhibitor of TNNI3K [34].…”
Section: Discussionmentioning
confidence: 99%
“…This can be used to increase potency on target and enhance selectivity over other kinases/targets. Cardiac troponin Iinteracting kinase (TNNI3K) [50][51] and Spleen tyrosine kinase (Syk) 52 have both utilised this to increase potency (by 60-160-fold) and selectivity by the addition of a nitrogen (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…[45] All other reagents were available from Enamine Ltd. 1 H, 13 [44] [49] When organic solutions were concentrated under reduced pressure, a 35-40°C bath was used.…”
Section: Methodsmentioning
confidence: 99%